Giving and Forgiving in Nietzsche and Derrida - Lemm, Vanessa (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article makes a contribution to the current debate on forgiveness and gift-giving incontemporary political and social philosophy. This article presents Nietzsche’s conception of forgivenessas gift-giving beginning with Nietzsche’s critique of the Christian practice of forgiveness as an exampleof the spirit of revenge in order to then point out the affinities between the Nietzschean critique andwhat Derrida names ‘impure’ or ‘conditional’ forgiveness. It argues that overcoming revenge or ‘impureforgiveness’ requires an affirmation of the animality of the human being as a life force indispensable tothe constitution of free and just forms of social and political life.
Keywords: forgiveness; gift; Nietzsche; Derrida; justice; animality